Fluorescence Correlation Spectroscopy Reveals Survival Motor Neuron Oligomerization but No Active Transport in Motor Axons of a Zebrafish Model for Spinal Muscular Atrophy - Koh, Angela; Sarusie, Menachem Viktor; Ohmer, Jürgen; Fischer, Utz; Winkler, Christoph; Wohland, Thorsten (Frontiers in Cell and Developmental Biology, 2021)
Spinal Muscular Atrophy (SMA) is a progressive neurodegenerative disease affecting lower motor neurons that is caused by a deficiency in ubiquitously expressed Survival Motor Neuron (SMN) protein. Two mutually exclusive hypotheses have been discussed to explain increased motor neuron vulnerability in SMA. Reduced SMN levels have been proposed to lead to defective snRNP assembly and aberrant splicing of transcripts that are essential for motor neuron maintenance. An alternative hypothesis proposes a motor neuron-specific function for SMN in axonal transport of mRNAs and/or RNPs. To address these possibilities, we used a novel in vivo approach with fluorescence correlation spectroscopy (FCS) in transgenic zebrafish embryos to assess the subcellular dynamics of Smn in motor neuron cell bodies and axons. Using fluorescently-tagged Smn we show that it exists as two freely diffusing components, a monomeric, and a complex-bound, likely oligomeric, component. This oligomer hypothesis was supported by the disappearance of the complex-bound form for a truncated Smn variant that is deficient in oligomerization and a change in its dynamics under endogenous Smn deficient conditions. Surprisingly, our FCS measurements did not provide any evidence for an active transport of Smn in axons. Instead, our in vivo observations are consistent with previous findings that SMN acts as a chaperone for the assembly of snRNP and mRNP complexes.